At the Crossroads of Fear, Confusion and Hope. COVID-19 News as the Motivator of Affective News Usage and Sense-Making Practices - Tuomola, Salla; Hujanen, Jaana; Lehtisaari, Katja; Ruotsalainen, Juho; Grönlund, Mikko (Routledge, 2025)
This study explores Finnish media users’ emotional and affective experiences of being exposed to news and communication regarding COVID-19 during the pandemic. To identify their emotions and subsequent affective news usage and sense-making practices, we conducted 14 semi-structured interviews, which we analysed qualitatively using thematic categorisation. The interview data revealed five most common emotions – fear, confusion, frustration, anger, and hope – and connections between these emotions and various affective news usage practices. Ten distinct affective practices also emerged, among them a thirst for up-to-date knowledge, self-protection from news and conflicting opinions, adaptation to the new everyday life, resistance to restrictions and people with clashing opinions, and acting responsibly for the common good. We then analysed how the experienced emotions and affective practices influenced the trust in and willingness to engage with mainstream media during the pandemic. When the news coverage engendered strong affective reactions, interviewees felt compelled to criticise the mainstream news, especially if their trust in traditional news media was already low before the pandemic. Accordingly, if they found the news coverage overwhelming and intimidating, they sought counter-information for an alternative interpretation of the experience of disruption to everyday life.